2000
DOI: 10.1038/35039512
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian sodium channel BNC1 is required for normal touch sensation

Abstract: Of the vertebrate senses, touch is the least understood at the molecular level The ion channels that form the core of the mechanosensory complex and confer touch sensitivity remain unknown. However, the similarity of the brain sodium channel 1 (BNC1) to nematode proteins involved in mechanotransduction indicated that it might be a part of such a mechanosensor. Here we show that disrupting the mouse BNC1 gene markedly reduces the sensitivity of a specific component of mechanosensation: low-threshold rapidly ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
421
2
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 463 publications
(447 citation statements)
references
References 27 publications
18
421
2
3
Order By: Relevance
“…Dorsal Root Ganglia (DRG) Neuron Electrophysiology. Mouse DRG neurons were cultured from C57BL͞6 mice as described (7,25). Cells were incubated overnight at room temperature or at 37°C.…”
Section: Cos-7 Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Dorsal Root Ganglia (DRG) Neuron Electrophysiology. Mouse DRG neurons were cultured from C57BL͞6 mice as described (7,25). Cells were incubated overnight at room temperature or at 37°C.…”
Section: Cos-7 Cellmentioning
confidence: 99%
“…In Caenorhabditis elegans, the DEG͞ENaC channel subunits MEC-4 and MEC-10 are expressed in touch cell neurons, where they are thought to form part of the mechanoreceptor complex (3). In mammals, the DEG͞ENaC channel BNC1 (4) [also called MDEG (5), BNaC1 (6), and ASIC2 (2)] is expressed in lanceolate nerve endings at the site of mechanotransduction (7). Targeted disruption of the BNC1 gene in mice reduced the sensitivity of low-threshold, rapidly adapting mechanoreceptors, indicating that BNC1 is required for normal touch sensation (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of ASIC2 null mice showed that ASIC2 was a central component of a mechanosensory complex (Price et al, 2000). However, a study of ASIC2 gene knockout in the mouse suggested that ASIC2 was not part of a mechanically gated cation channel important for cutaneous mechanosensation, Summary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that ASICs are involved in a wide range of neuronal functions such as synaptic plasticity (Wemmie et al 2003), mechanosensation (Price et al 2000;, nociception linked to local tissue acidosis, sour-taste reception (Ugawa et al 1998), and the modulation of retinal and cochlear functions (Ettaiche et al 2004). It is also known that ASICs respond to an extracellular pH lower than 7.0.…”
Section: Introductionmentioning
confidence: 99%